Rehabilitation of Worn Dentition with Direct Resin Composite Restorations: A Case Report - Marta Blasi Beriain; Giovanni Tommaso Rocca; Leonardo Franchini; Didier Dietschi; Carlo Massimo Saratti (MDPI AG, 2022)
The incidence of tooth wear has steadily increased in all Western populations during the past decades. A through-care strategy, extendable for a lifetime, has become crucial to prevent the extensive loss of sound dental structure and to make an eventual retreatment affordable in the long term. An interceptive treatment using resin composite materials and no-preparation approaches meets these requirements. Moreover, continual developments in digital dentistry makes possible to predict the treatment plan for the restorative rehabilitation of the mouth. The availability of digital resources allows clinicians to increase predictability for excellent esthetics and good functional results. This article provides a step-by-step description of a full-mouth additive rehabilitation achieved by employing digital workflows and direct resin composite restorations. A comprehensive functional and esthetic evaluation of the treatment is proposed and discussed.